Power System Resiliency: A Comprehensive Overview from Implementation Aspects and Innovative Concepts - Erenoglu, Ayse Kubra; Sengor, Ibrahim; Erdinc, Ozan (ELSEVIER, 2024)
The bulk electrical system, a critical infrastructure for societal functionality, must meet the electricity demands of end-users sustainably, economically, and in compliance with standards. The concept of power system resiliency has gained significant attention as vulnerabilities and potential attacks could lead to substantial losses. This paper distinguishes power system resiliency from reliability through a detailed literature review. It discusses the development of quantitative metrics from operational and infrastructural perspectives to better understand this emerging concept. We categorize the threats into natural disasters and cyber threats, evaluating their impacts on power system components. The integration of smart grid technologies-including demand response, electric vehicles, distributed generation, energy storage systems, and microgrids-is explored to demonstrate how they enhance resilience against external shocks. This review not only offers a comprehensive analysis of load restoration techniques through smart grid practices but also identifies future challenges, such as adapting to increasingly severe climate conditions, advancing cybersecurity measures to match evolving threats, and ensuring the scalability of resilient systems to meet growing energy demands. These challenges highlight the necessity for innovative research and strategic planning to strengthen power systems against a broad spectrum of emerging threats. This work serves as a critical reference for researchers and planners dedicated to enhancing resiliency strategies.
Keywords: demand response; distributed generation; microgrid; resiliency; smart grid; vulnerabilities; SERVICE RESTORATION; ENERGY MANAGEMENT; RENEWABLE ENERGY; IMPACT ASSESSMENT; GRID RESILIENCE; ENHANCEMENT; MICROGRIDS; SECURITY; RECONFIGURATION; Energy & Fuels; Environmental Sciences & Ecology